Talent management and public service competitiveness in Malaysia - Syahrul Idzuan Mohamad,; Nur Riza Mohd Suradi,; Zamira Hasanah Zamzuri,; Siti Norafidah Mohd Ramli, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Public service organizations in Malaysia must improve their performance and competitiveness to safeguard themselves against the potential negative consequences of their modest decline in these areas. Previous studies have recognized that talent management can significantly influence an organization's performance, but theoretical and empirical research on this relationship remains limited within public service organizations. Therefore, this research aimed to explore and understand the interplay among talent, talent management, and competitiveness within the context of the Malaysian public service sector. Following a qualitative approach, interviews were conducted with 10 Malaysian public servants from the Public Sector Key Position (JUSA) level. The interview transcripts were subsequently analyzed using ATLAS.ti 9 software. The study's findings revealed that talent management and talent constitute a core strategy for competitiveness in the Malaysian public service. Clear definitions of these concepts are vital in facilitating a more profound understanding of this strategy among public service organizations and their stakeholders. Consequently, the refinement and elaboration of definitions are essential to ensure clarity and consensus among all stakeholders, thus preventing confusion and misunderstandings in the future. Lastly, the definition process enables public service organizations to develop more precise definitions based on their specific context and scope.